Synthesis of triphenylene-fused phosphole oxides via C–H functionalizations - Rahman, Md. Shafiqur; Yoshikai, Naohiko (Beilstein Journal of Organic Chemistry, 2020)
The synthesis of triphenylene-fused phosphole oxides has been achieved through two distinct C–H functionalization reactions as key steps. The phosphole ring was constructed by a three-component coupling of 3-(methoxymethoxy)phenylzinc chloride, an alkyne, and dichlorophenylphosphine, involving the regioselective C–H activation of the C2 position of the arylzinc intermediate via 1,4-cobalt migration. The resulting 7-hydroxybenzo[b]phosphole derivative was used for further π-extension through Suzuki–Miyaura couplings and a Scholl reaction, the latter closing the triphenylene ring. The absorption and emission spectra of the thus-synthesized compounds illustrated their nature as hybrids of triphenylene and benzo[b]phosphole.
Keywords: C–H functionalization; fluorescence; phosphole; polycyclic aromatic hydrocarbons; triphenylene

(untitled) - Baumgartner, T.; Réau, R. (Chem. Rev., 2006)

(untitled) - Crassous, J.; Réau, R. (Dalton Trans., 2008)

(untitled) - Matano, Y.; Imahori, H. (Org. Biomol. Chem., 2009)

(untitled) - Ren, Y.; Baumgartner, T. (Dalton Trans., 2012)

(untitled) - Baumgartner, T. (Acc. Chem. Res., 2014)

(untitled) - Stolar, M.; Baumgartner, T. (Chem. – Asian J., 2014)

(untitled) - Duffy, M. P.; Delaunay, W.; Bouit, P.-A.; Hissler, M. (Chem. Soc. Rev., 2016)

(untitled) - Shameem, M. A.; Orthaber, A. (Chem. – Eur. J., 2016)

(untitled) - Hibner-Kulicka, P.; Joule, J. A.; Skalik, J.; Bałczewski, P. (RSC Adv., 2017)

(untitled) - Wang, C.; Fukazawa, A.; Taki, M.; Sato, Y.; Higashiyama, T.; Yamaguchi, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Wang, C.; Taki, M.; Sato, Y.; Fukazawa, A.; Higashiyama, T.; Yamaguchi, S. (J. Am. Chem. Soc., 2017)

(untitled) - Yavari, K.; Moussa, S.; Ben Hassine, B.; Retailleau, P.; Voituriez, A.; Marinetti, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Yavari, K.; Aillard, P.; Zhang, Y.; Nuter, F.; Retailleau, P.; Voituriez, A.; Marinetti, A. (Angew. Chem., Int. Ed., 2014)

(untitled) - Yavari, K.; Delaunay, W.; De Rycke, N.; Reynaldo, T.; Aillard, P.; Srebro-Hooper, M.; Chang, V. Y.; Muller, G.; Tondelier, D.; Geffroy, B.; Voituriez, A.; Marinetti, A.; et al. (Chem. – Eur. J., 2019)

(untitled) - Furukawa, S.; Suda, Y.; Kobayashi, J.; Kawashima, T.; Tada, T.; Fujii, S.; Kiguchi, M.; Saito, M. (J. Am. Chem. Soc., 2017)

(untitled) - Rahman, M. S.; Yoshikai, N. (Org. Lett., 2019)

(untitled) - Wu, B.; Santra, M.; Yoshikai, N. (Angew. Chem., Int. Ed., 2014)

(untitled) - Wakatsuki, A.; Yukimoto, M.; Minoura, M.; Fujii, K.; Kimura, Y.; Matano, Y. (Dalton Trans., 2018)

(untitled) - Watson, M. D.; Fechtenkötter, A.; Müllen, K. (Chem. Rev., 2001)

(untitled) - Pérez, D.; Guitián, E. (Chem. Soc. Rev., 2004)

(untitled) - Kumar, S. (Chem. Soc. Rev., 2006)

(untitled) - Sergeyev, S.; Pisula, W.; Geerts, Y. H. (Chem. Soc. Rev., 2007)

(untitled) - Alam, M. A.; Motoyanagi, J.; Yamamoto, Y.; Fukushima, T.; Kim, J.; Kato, K.; Takata, M.; Saeki, A.; Seki, S.; Tagawa, S.; Aida, T. (J. Am. Chem. Soc., 2009)

(untitled) - Percec, V.; Imam, M. R.; Peterca, M.; Wilson, D. A.; Graf, R.; Spiess, H. W.; Balagurusamy, V. S. K.; Heiney, P. A. (J. Am. Chem. Soc., 2009)

(untitled) - Badjic, J. D.; Ronconi, C. M.; Stoddart, J. F.; Balzani, V.; Silvi, S.; Credi, A. (J. Am. Chem. Soc., 2006)

(untitled) - Wang, S.; Yan, C.; Shang, J.; Wang, W.; Yuan, C.; Zhang, H.-L.; Shao, X. (Angew. Chem., Int. Ed., 2019)

(untitled) - Wu, B.; Chopra, R.; Yoshikai, N. (Org. Lett., 2015)

(untitled) - Aillard, P.; Gicquel, M.; Yavari, K.; Retailleau, P.; Voituriez, A.; Marinetti, A. (Eur. J. Org. Chem., 2018)

(untitled) - Tan, B.-H.; Dong, J.; Yoshikai, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Grzybowski, M.; Skonieczny, K.; Butenschön, H.; Gryko, D. T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Rieger, R.; Müllen, K. (J. Phys. Org. Chem., 2010)

(untitled) - Verbitskiy, E. V.; Eltsov, O. S.; Zhilina, E. F.; Pakhomov, I. M.; Rusinov, G. L.; Chupakhin, O. N.; Charushin, V. N. (Tetrahedron, 2019)

(untitled) - Schwab, M. G.; Qin, T.; Pisula, W.; Mavrinskiy, A.; Feng, X.; Baumgarten, M.; Kim, H.; Laquai, F.; Schuh, S.; Trattnig, R.; List, E. J. W.; Müllen, K. (Chem. – Asian J., 2011)

(untitled) - Yoshikai, N.; Santra, M.; Wu, B. (Organometallics, 2017)

(untitled) - Wu, B.; Yoshikai, N. (Org. Biomol. Chem., 2016)

(untitled) - Chen, Y.-R.; Duan, W.-L. (J. Am. Chem. Soc., 2013)

(untitled) - Unoh, Y.; Hirano, K.; Satoh, T.; Miura, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Quint, V.; Morlet-Savary, F.; Lohier, J.-F.; Lalevée, J.; Gaumont, A.-C.; Lakhdar, S. (J. Am. Chem. Soc., 2016)

(untitled) - Liu, W.-Q.; Lei, T.; Zhou, S.; Yang, X.-L.; Li, J.; Chen, B.; Sivaguru, J.; Tung, C.-H.; Wu, L.-Z. (J. Am. Chem. Soc., 2019)